Effect of Porphyromonas gingivalis Infection on Healing of Skeletal Muscle Injury: An In Vivo Study - Shintaro Shimizu; Kairi Hayashi; Yasuo Takeuchi; Gen Tanabe; Hiroshi Churei; Hiroaki Kobayashi; Toshiaki Ueno; Kenji Fueki (MDPI AG, 2024)
Background/Objectives:Porphyromonas gingivalis infection has been associated with various systemic diseases and may cause delayed healing of muscle injury. However, the relationship between muscle injury healing and P. gingivalis infection remains unclear. Our hypothesis was that P. gingivalis infection delays the healing of muscle injuries. Methods: Fifty-six 8-week-old male Wistar rats were randomly divided into two groups: sonicated P. gingivalis was intraperitoneally administered in one group (PG group), whereas saline was administered in the other group (CO group). Skeletal muscle injury was induced via cardiotoxin injections in all animals. The cross-sectional area of regenerating muscle cells was evaluated by haematoxylin-eosin staining, and the degree of muscle fibrosis was evaluated by Masson's trichrome staining. The expression of paired box protein (Pax7) and myoblast determination protein (MyoD) and the identified stages of myocyte regeneration were analysed by immunohistochemical staining. Motion analysis was performed during walking. Results: The cross-sectional area of muscle cells was significantly smaller in the PG group on days 7 and 14 post-injury than in the CO group. The Pax7+/MyoD− ratio was significantly lower in the PG group on day 1 post-injury than in the CO group. Motion analysis of treadmill walking showed that the PG group had a lower minimum calcaneal height on days 3 and 7 post-injury than the CO group. Conclusions: This study suggests that administration of sonicated P. gingivalis in rats can delay the healing process of muscle injury. Further research is needed to understand this mechanism of delay of P. gingivalis.